Loison-Charles, J. (2023). Vladimir Nabokov as an Author-Translator: Writing and Translating between Russian, English and French. Bloomsbury Academic. http://doi.org/10.5040/9781350243316 (pp. 266) - Yuan, Limei (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2023)
Book review